Tempered martensite-containing hot-rolled wire rod for high-strength strand and method for manufacturing the same
Patent Information
- Application Number
- CN202611047298.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-15
AI Technical Summary
[0003]目前,现有的珠光体类型钢绞线强度等级不超过1960MPa,至于2500MPa级超高强度等级,受斯太尔摩风冷线的控冷能力限制,则面临母材网状碳化物、马氏体等异常组织不可控,导致拉丝断丝风险急剧提升的问题
[0024](1)针对现有高强绞线用热轧盘条生产时网状碳化物、马氏体等异常组织不可控,强塑性不足或难以兼顾生产效率的问题,本发明采用Nb-V-Mo化学成分设计结合在线熔盐快淬等温韧化技术,控制盘条经过前段熔盐处理,快速从高温奥氏体状态进入马氏体相区,抑制网状碳化物并形成以淬火马氏体为主的组织,再经过后段熔盐处理促进未转变的残余奥氏体分解转变为索氏体,并对淬火组织进行等温回火,促进微合金碳化物弥散分布,以快速调控盘条的强塑性匹配,随后经过辊道缓冷促进盘条组织进一步韧化,可提高盘条回火软化效果,形成含回火马氏体热轧盘条,促进热轧盘条高效稳定生产,具有良好的工业适应性。
Smart Images

Figure CN122542776B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hot-rolled wire rod technology, specifically relating to a high-strength stranded wire rod containing tempered martensite and its manufacturing method. Background Technology
[0002] With the large-scale construction of infrastructure and high-speed railways, the use of prestressed steel strands as the main stress-bearing tool is increasing day by day. Lightweighting and ultra-high strength have become important development directions for steel strands. Therefore, it is required that the strength grade of hot-rolled wire rod base material for ultra-high strength strands be further improved.
[0003] Currently, the strength grade of existing pearlitic steel strands does not exceed 1960MPa. As for the ultra-high strength grade of 2500MPa, due to the limited cooling capacity of the Stellmore air-cooled line, it faces the problem of uncontrollable abnormal structures such as network carbides and martensite in the base material, which leads to a sharp increase in the risk of wire breakage during drawing. If offline heat treatment is used, such as the 2500MPa grade steel strand wire rod and its manufacturing method disclosed in patent CN112176258B, which uses a C-Si-Mn-Cr-Al-V-Ti composition design, after hot rolling into wire, it needs to go through Stellmore cooling, coiling, and salt bath cooling in sequence before being coiled into wire rod. Offline heat treatment involves rewinding after coiling, offline heat treatment, and salt bath, which faces the problems of many processes, long cycle, and a sharp increase in production costs and energy consumption. If there is too much martensite, it will also cause brittle fracture of the coil, affecting stable production. Therefore, it is necessary to develop a 2500MPa grade ultra-high strength strand hot-rolled wire rod and its manufacturing method to effectively control abnormal structure, achieve efficient and stable production, reduce the risk of wire breakage, and eliminate the need for offline heat treatment.
[0004] Although existing technologies disclose solutions using online salt bath treatment, such as the 2500~2560MPa grade stress corrosion resistant prestressed steel strand wire rod, steel strand and production method disclosed in patent CN120400683A, which adopts a C-Si-Mn-Cr-V-Nb composition design and combines online salt bath isothermal treatment after wire drawing with online annealing in an annealing furnace to obtain sorbite wire rod, the one-stage online salt bath isothermal treatment and the pearlite type hot-rolled wire rod matrix still pose a risk of abnormal grain boundary cementite and martensite structure, which increases the risk of wire breakage during strand manufacturing. At the same time, it also requires long-term annealing treatment, which affects production energy consumption and efficiency. Summary of the Invention
[0005] This invention aims to at least partially solve one of the above-mentioned technical problems. This invention provides a hot-rolled wire rod containing tempered martensite for high-strength stranded wire and its manufacturing method, which can effectively suppress abnormal network carbides, achieve multiphase structure control and rapidly control the structure toughness online. It can be used for the production of ultra-high strength stranded wires such as 2500MPa grade, without the need for offline heat treatment and can reduce the risk of wire breakage.
[0006] The technical solution adopted by this invention to solve its technical problem is:
[0007] The first aspect of this invention is to provide a method for manufacturing hot-rolled wire rod containing tempered martensite for high-strength stranded wire, the method comprising:
[0008] The hot-rolled wire rod is rolled into production line material according to its chemical composition. The chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.95%~0.99%, Si: 0.87%~1.05%, Mn: 0.91%~1.12%, Cr: 0.45%~0.65%, Nb: 0.025%~0.040%, V: 0.025%~0.040%, Mo: 0.35%~0.55%, P≤0.015%, S≤0.015%, with the remainder being Fe and unavoidable impurities.
[0009] The wire rod is produced by spinning into coils and then undergoes online molten salt rapid quenching isothermal toughening treatment. The coils first undergo a preliminary molten salt treatment with a cooling rate of ≥30℃ / s. The temperature of the coil entering the salt bath in the preliminary molten salt treatment is 870~940℃, the molten salt temperature is 280~350℃, and the treatment time is 5~15s. Then, it undergoes a subsequent molten salt treatment with a molten salt temperature of 560~600℃ and a treatment time of 160~360s. Finally, it undergoes slow cooling on a roller conveyor, where the coils are slowly cooled to 280℃ or below at a cooling rate of 0.25~0.55℃ / s, resulting in a hot-rolled coil with a microstructure consisting of tempered sorbite, tempered martensite, and ferrite.
[0010] In a preferred embodiment, a rectangular steel billet with a side length of 180mm to 220mm is heated before rolling. During heating, the uniform heating temperature of the heating furnace is controlled at 1150 to 1220℃, and the furnace time is 150 to 280 minutes.
[0011] In the preferred technical solution, the initial rolling temperature is controlled at 1040~1090℃, the final rolling temperature is controlled at 900~940℃, and the final rolling reduction is 23%~28%.
[0012] In a preferred embodiment, the spinning temperature during spinning is 890~930℃.
[0013] In a preferred embodiment, the wire is coiled and then conveyed to the salt tank via a roller conveyor with a speed of 0.7~1.1m / s.
[0014] In a preferred embodiment, the roller speed of the front-end molten salt treatment is 0.4~0.7m / s.
[0015] In the preferred technical solution, the molten salt circulation rate of the front-end molten salt treatment is 640~840t / h, and the molten salt temperature rise is ≤10℃.
[0016] In a preferred embodiment, the roller speed of the downstream molten salt treatment is 0.5~0.8 m / s.
[0017] In the preferred technical solution, the molten salt circulation rate of the downstream molten salt treatment is 450~650t / h, and the molten salt temperature rise is ≤3℃.
[0018] In the preferred technical solution, during the slow cooling of the roller conveyor, the wire rod enters the conveyor roller conveyor after exiting the salt tank. The heat preservation cover on the conveyor roller conveyor is closed or the opening of the heat preservation cover is controlled, and the hot air at ≥265℃ from the salt tank is blown onto the conveyor roller conveyor.
[0019] A second aspect of the present invention is to provide a hot-rolled wire rod containing tempered martensite for high-strength stranded wire, wherein the hot-rolled wire rod is manufactured by the manufacturing method of any one of the above-described methods for manufacturing hot-rolled wire rod containing tempered martensite for high-strength stranded wire.
[0020] In the preferred embodiment, the diameter of the hot-rolled wire rod is 5.5~16mm, the volume fraction of tempered sorbite is 32%~44%, the lamellar spacing of the tempered sorbite is 50~70nm, and the volume fraction of tempered martensite is 55%~65%.
[0021] In the preferred embodiment, the hot-rolled wire rod has a network carbide level of 0 and a mechanical property difference of ≤50MPa between coils.
[0022] In the preferred embodiment, the hot-rolled wire rod has a tensile strength of 1623~1673MPa and a reduction of area of 31%~36%.
[0023] Compared with the prior art, the beneficial effects of the present invention are at least as follows:
[0024] (1) In view of the problems of uncontrollable abnormal structures such as network carbides and martensite in the production of hot-rolled wire rods for high-strength strands, insufficient strength and plasticity or difficulty in balancing production efficiency, the present invention adopts Nb-V-Mo chemical composition design combined with online molten salt rapid quenching isothermal toughening technology to control the wire rod to quickly enter the martensite phase region from the high-temperature austenitic state after the first stage of molten salt treatment, suppressing network carbides and forming a structure mainly composed of quenched martensite. Then, after the second stage of molten salt treatment, the untransformed residual austenite is decomposed into sorbite, and the quenched structure is isothermally tempered to promote the dispersion distribution of microalloyed carbides, so as to quickly control the strength and plasticity matching of the wire rod. Subsequently, the wire rod structure is further toughened by slow cooling on the roller table, which can improve the tempering softening effect of the wire rod and form a hot-rolled wire rod containing tempered martensite, promoting the efficient and stable production of hot-rolled wire rods and having good industrial adaptability.
[0025] (2) In view of the problems of high cost, insufficient strength and plasticity, large fluctuation of mechanical properties and the need for offline heat treatment of existing hot-rolled wire rod materials for high-strength stranded wire, the microstructure of the present invention includes a multiphase structure composed of tempered sorbite, tempered martensite and ferrite. Tempered martensite has a high dislocation density and strength characteristics, and at the same time significantly improves brittleness compared with martensite. It can avoid the coarse lamellar pearlite structure in the core. Tempered sorbite has good strength and plasticity. After sufficient phase transformation and online toughening, the hot-rolled wire rod can reach the network carbide level of 0, the mechanical property difference between the same coil ≤50MPa, the tensile strength is 1623~1673MPa, and the reduction of area is 31%~36%. It can effectively suppress the abnormal network carbide, realize the control of multiphase structure and quickly control the structure toughness online. It has excellent drawing processing performance and can be used for the production of ultra-high strength stranded wire such as 2500MPa grade. It does not require offline heat treatment and can reduce the risk of wire breakage. Attached Figure Description
[0026] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:
[0027] Figure 1 This is a metallographic diagram of Embodiment 1 of the present invention.
[0028] Figure 2 This is a metallographic diagram of Embodiment 2 of the present invention.
[0029] Figure 3 This is a metallographic diagram of Embodiment 3 of the present invention. Detailed Implementation
[0030] The embodiments described below with reference to the accompanying drawings are exemplary and are merely for illustrative purposes and do not limit the description of the features and characteristics of the invention. They are intended to provide the best mode for carrying out the invention, to explain the invention, and to enable those skilled in the art to practice the invention. However, they should not be construed as limiting the scope of the invention in any way, which is defined only by the appended claims. The microstructure and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples includes: tensile testing using GB-T228.1-2021 Metallic Materials - Tensile Testing - Part 1: Room Temperature Test Method, to obtain tensile strength and reduction of area; microstructure testing using the metal microstructure testing method of GB / T13298 standard; and mechanical property same-coil difference test method: two coils of wire rod are taken 5m from the end of the coil. Using the overlap area as the base point, each coil of wire rod is divided into 8 equal segments. One tensile specimen is taken from each segment. The difference in strength of the tensile specimens after tensile testing is the mechanical property same-coil difference.
[0031] Currently, the strength grades of existing pearlitic steel strands do not exceed 1960 MPa. For ultra-high strength grades of 2500 MPa, the uncontrollable abnormal microstructures such as network carbides and martensite in the hot-rolled wire rod base material lead to a sharp increase in the risk of wire breakage during drawing. Offline heat treatment, on the other hand, faces the problem of drastically increased production costs and energy consumption. This invention addresses this issue by combining Nb-V-Mo chemical composition design with online molten salt rapid quenching isothermal toughening technology to achieve online control of microstructure and toughness for efficient production, eliminating the need for offline heat treatment. The high-strength strand described in this invention is a relatively advanced method using tempered martensite-containing hot-rolled wire rod. In a preferred embodiment, the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.95%~0.99%, Si: 0.87%~1.05%, Mn: 0.91%~1.12%, Cr: 0.45%~0.65%, Nb: 0.025%~0.040%, V: 0.025%~0.040%, Mo: 0.35%~0.55%, P≤0.015%, S≤0.015%, with the remainder being Fe and unavoidable impurities; the microstructure of the hot-rolled wire rod includes a multiphase structure composed of tempered sorbite, tempered martensite, and ferrite.
[0032] The chemical composition and mass percentage of the above-mentioned hot-rolled wire rods are designed based on the following:
[0033] (1) Carbon: C is an effective strengthening element with a relatively low price. It can enhance the strength of the matrix through solid solution strengthening and control the critical cooling rate of martensite transformation. It can obtain a sufficient amount of martensite under molten salt rapid quenching conditions. At the same time, carbon forms alloy carbides with alloying elements such as Cr, Mo, Nb, and V, which can produce a second-phase strengthening effect. In the subsequent cold drawing and large deformation process, it continuously improves the work hardening efficiency. However, excessive C content will increase carbon segregation. The segregated area is prone to forming network carbides, which increases the difficulty of controlling the uniformity of the structure. At the same time, the martensite distortion increases, causing a decrease in plasticity and toughness. Therefore, in order to balance the high strength and plasticity and toughness control of 2500MPa grade stranded wire, the mass percentage of C is controlled at 0.95%~0.99%.
[0034] (2) Silicon: Si is a solid solution strengthening element of ferrite. It can inhibit the diffusion of carbon atoms, prevent the coarsening of cementite lamellars, delay the transformation of pearlite, help to form sufficient martensite structure during molten salt rapid quenching, and improve tempering stability. However, excessive silicon will increase the surface decarburization tendency, increase the high temperature deformation resistance of steel, increase the cold work hardening tendency of steel, and improve the drawing deformation resistance. Therefore, in order to match the molten salt rapid quenching isothermal toughening process and take into account both tempering stability and cold workability, the mass percentage of Si is controlled at 0.87%~1.05%.
[0035] (3) Manganese: Mn can produce a certain solid solution strengthening effect, expand the austenite phase region, reduce the austenite transformation temperature, shift the C curve to the right, improve the hardenability of steel, promote the formation of martensite and make the core of the wire rod also obtain a uniform structure, and avoid the formation of coarse pearlite structure in the core of the wire rod. However, when the Mn content is too high, it will increase the segregation of alloying elements during the solidification process of the billet, resulting in increased fluctuations in mechanical properties. At the same time, it will promote the generation of temper brittleness and easily lead to a decrease in the impact toughness of steel during isothermal treatment. Therefore, in order to fully transform the hot-rolled wire rod and take into account both the uniformity of the structure and the control of the multiphase structure, the mass percentage of Mn is controlled at 0.91%~1.12%.
[0036] (4) Chromium: Cr element reduces the rate of austenite to pearlite transformation, causing the C curve to shift significantly to the right, which significantly improves the hardenability of steel and promotes the acquisition of sufficient martensite structure in wire rod during molten salt rapid quenching. It works synergistically with Mn to reduce the interlamellar spacing of sorbite, so that martensite can still maintain a high dislocation density and fine microstructure at higher tempering temperatures. At the same time, the alloy carbides formed by chromium and carbon have high hardness and good stability, and are not easy to grow during tempering, which can reduce strength loss. However, excessive Cr content will aggravate the risk of element segregation, making the sorbite transformation too slow, resulting in excessively long isothermal treatment time and reduced production efficiency. Therefore, in order to control the multiphase structure and improve the resistance to tempering softening, the mass percentage of Cr is controlled at 0.45%~0.65%.
[0037] (5) Niobium: As a microalloying element, Nb will be precipitated in the form of carbonitrides during hot rolling, which will inhibit the growth of austenite grains and provide high-density nucleation sites for subsequent phase transformation. Excess Nb can be dispersed and precipitated during isothermal processes, and will work with V to rapidly strengthen the matrix, make up for the strength loss during isothermal processes, and improve the work hardening efficiency during large deformation of cold drawing. However, the cost of Nb is relatively high, and excessive addition is not conducive to controlling material costs and improving the high-temperature deformation resistance of steel. Therefore, the mass percentage of Nb is controlled at 0.025%~0.040%.
[0038] (6) Vanadium: As a microalloying element, V can be precipitated in the high-temperature hot rolling process to pin the austenite grain boundaries and inhibit the high-temperature coarsening of austenite grains. Excess V can be dispersed and precipitated in the medium-temperature isothermal process to improve the fracture toughness of steel, enhance the strength of the matrix without sacrificing the plasticity of the matrix, and improve the work hardening efficiency in the cold drawing large deformation process. However, V is relatively expensive, and excessive addition is not conducive to controlling material costs. At the same time, it increases the risk of coarsening and may become a crack source in the matrix. Therefore, the mass percentage of V is controlled at 0.025%~0.040%.
[0039] (7) Molybdenum: The addition of Mo strongly inhibits the pearlite transformation, causing the pearlite transformation curve to shift to the right. It can reduce the diffusion ability of carbide-forming elements, thereby delaying the formation of carbide precipitation and inhibiting the precipitation of related second-phase particles. This can prevent the precipitated phase from ripening and growing at high temperatures, so that the alloy carbides are finely dispersed during isothermal treatment, improving tempering stability. However, excessive Mo content is not conducive to controlling material costs, and at the same time, the ductility and toughness decrease. Therefore, the mass percentage of Mo is controlled at 0.35%~0.55%.
[0040] (8) Phosphorus and sulfur: P and S are impurity elements, and the lower the better. Therefore, P ≤ 0.015% and S ≤ 0.015% should be controlled.
[0041] The hot-rolled wire rods mentioned above adopt an Nb-V-Mo chemical composition design. The addition of trace amounts of Nb and V can control material costs. C provides a solid solution strengthening basis, and the optimized composition ratio of Si, Mn, and Cr controls the hardenability of the steel body and inhibits cementite coarsening. The microalloying of Nb and V provides grain refinement and second-phase strengthening effects, while Mo inhibits the ripening of alloy carbides. This provides favorable conditions for promoting the formation of a sufficient amount of martensite under rapid quenching, inhibiting coarse pearlite in the core, controlling the resistance to tempering softening, and ensuring efficient and stable production.
[0042] The manufacturing method of the above-mentioned hot-rolled wire rod includes: rolling the wire rod into a production line according to the chemical composition of the hot-rolled wire rod; after the wire rod is produced into a wire rod, it undergoes online molten salt rapid quenching isothermal toughening treatment, in which the wire rod first undergoes a pre-stage molten salt treatment and is cooled at a cooling rate of ≥30℃ / s, the temperature of the wire rod entering the salt bath in the pre-stage molten salt treatment is 870~940℃, the molten salt temperature is 280~350℃, and the treatment time is 5~15s; then it undergoes a post-stage molten salt treatment, the molten salt temperature in the post-stage molten salt treatment is 560~600℃, and the treatment time is 160~360s; finally, it undergoes slow cooling on a roller table, in which the wire rod is slowly cooled to 280℃ or below at a cooling rate of 0.25~0.55℃ / s, resulting in a hot-rolled wire rod with a microstructure consisting of tempered sorbite, tempered martensite, and ferrite, which are multiphase structures.
[0043] The above-mentioned hot-rolled wire rods are treated with molten salt rapid quenching isothermal toughening based on the Nb-V-Mo chemical composition:
[0044] Firstly, compared to the limitations of Stellmore air cooling's maximum cooling capacity and unstable temperature control, and the difficulty in controlling the appropriate phase transformation of network carbides and martensite under existing one-stage online salt bath treatment, molten salt offers several advantages. Firstly, molten salt has a higher heat transfer coefficient than air. The temperature of the molten salt during the initial molten salt treatment is lower than that of the molten salt during the isothermal phase transformation of sorbite. When the coiled wire enters the salt bath, its temperature can be maintained at a relatively high level of 870~940℃, avoiding premature precipitation of network carbides due to excessively low temperatures and the influence of high carbon content. Secondly, the molten salt treatment allows the wire to rapidly cool from a high-temperature austenitic state, bypassing the precipitation temperature range of secondary cementite, thus avoiding the formation of grain boundary cementite and network carbides that could rupture the matrix, lose the carbon source for phase transformation, and deteriorate ductility and toughness. Thirdly, when the wire passes through the molten salt, the molten salt can cover the coil... The wire rod exhibits uniform heat exchange on its surface, eliminating the temperature difference issues between the air-cooled and air-cooled surfaces, and between overlapping and non-overlapping areas, unlike the Stellmore air-cooling line. This prevents the formation of uncontrollable martensitic structures due to localized overcooling. Furthermore, the molten salt temperature in the initial molten salt treatment is lower than that in a single-stage salt bath treatment. Due to the hardenability of the wire rod, the transition from the high-temperature austenitic state to the martensitic phase region can be controlled. Rapid quenching results in a structure dominated by quenched martensite. The rapid formation of quenched martensite and the controllable phase transformation lead to a more uniform microstructure. Martensite also has a higher dislocation density and distortion than bainite and sorbite, which improves the matrix strength and resistance to tempering softening. It also avoids the coarsening of niobium and vanadium carbides caused by prolonged high-temperature periods or unstable temperature control in the Stellmore air-cooling line. This provides a foundation for the formation of multiphase structures and online toughening in the subsequent molten salt treatment.
[0045] Second, compared to the limitations of the Stellmore air-cooled line in terms of minimum cooling capacity, continuous cooling, and length, which makes it difficult to simultaneously achieve high-carbon, high-silicon phase transformation incubation, multiphase microstructure control, and online toughening, and the difficulty in achieving multiphase microstructure control and production efficiency under existing one-stage online salt bath treatment, the latter stage of molten salt treatment has a higher temperature than the former, which can increase the diffusion rate of carbon atoms, control the wire rod to enter the sorbite phase transformation, and promote the decomposition and transformation of the small amount of residual austenite that has not been transformed after the former molten salt treatment into sorbite microstructure. This can shorten the phase transformation incubation period and break down the phase transformation. To address the issues of prolonged phase transformation incubation and high structural stress under continuous cooling in high-carbon, high-silicon compositions, the wire rod gradually transforms to the molten salt temperature as the treatment time increases. This allows for a complete phase transformation, and, combined with the wire rod's hardenability, suppresses coarse pearlite in the core. Simultaneously, it prevents retained austenite from further forming martensite, bainite, and other low-temperature brittle abnormal structures during subsequent cooling. Furthermore, the temperature of the subsequent molten salt treatment can be appropriately increased, promoting isothermal tempering of the mixed structure of quenched martensite and sorbite at high temperatures. This is achieved by moderately reducing the dislocation preservation of the quenched martensite. By retaining strength characteristics and improving brittleness, the wire rod transforms into a tempered martensite structure that is both strong and tough. This is achieved by releasing structural stress and transitioning to an intermediate tempered sorbite structure with better ductility and toughness, while simultaneously allowing Nb and V carbides to disperse and precipitate during isothermal processes. Combined with Mo to inhibit the growth and maturation of precipitated phases at high temperatures, this rapidly strengthens and toughens the matrix, compensating for strength loss. This achieves multiphase microstructure control and rapid online toughening, solving the problems of high brittleness and high stress after phase transformation in quenched martensite, reducing the pressure of subsequent processing, and rapidly improving the strength-ductility balance of the wire rod. After exiting the salt bath, the strip is kept at a relatively high temperature. Slow cooling through the roller conveyor can further promote the toughening of the structure, but it is not necessary to use a long treatment with an excessively slow cooling rate. This can balance production efficiency and promote the efficient and stable production of hot-rolled wire rods, forming hot-rolled wire rods with a multiphase structure containing tempered martensite. This avoids brittle fracture during coiling, transportation and uncoiling caused by martensite, as well as the initiation and propagation of cracks due to network carbides, martensite and coarse carbides under drawing stress. It also improves the strength and plasticity and the uniformity of the structure, so as to produce ultra-high strength strands without offline heat treatment.
[0046] Furthermore, before rolling, the rectangular steel billet with a side length of 180mm~220mm is heated. During heating, the homogenization temperature of the heating furnace is controlled at 1150~1220℃, and the furnace time is 150~280min. By adopting appropriate homogenization temperature and furnace time, the rectangular steel billet can be austenitized, and carbon and all alloying elements can be fully dissolved in the austenite matrix, reducing the temperature difference between the inside and outside of the rectangular steel billet and avoiding the generation of large internal stress during rolling. At the same time, it avoids excessively high homogenization temperature or excessively long furnace time, which can lead to coarse austenite grains, surface decarburization, and oxidation burn-off.
[0047] Furthermore, during the rolling process, the initial rolling temperature is controlled at 1040~1090℃, the final rolling temperature at 900~940℃, and the final rolling reduction at 23%~28%. Controlling the initial rolling temperature can promote grain refinement and avoid excessive deformation resistance due to excessively low initial rolling temperature, which would increase the mill load. Conversely, it can avoid grain coarsening due to excessively high initial rolling temperature. By selecting appropriate rolling temperature and deformation amount, the strain-induced precipitation and grain refinement effects of Nb and V microalloying elements can be utilized to promote dynamic recrystallization and grain refinement during the final rolling process, thereby avoiding excessive final rolling reduction that exceeds the mill's load capacity or causes surface defects in the wire.
[0048] Furthermore, the wire drawing temperature during the drawing process is 890~930℃; after the rolled wire is drawn into coil by the wire drawing machine, it is conveyed by roller conveyor, which has a certain temperature drop. Controlling the wire drawing temperature can connect the final rolling temperature and the temperature of the coil entering the salt bath, avoiding excessively high wire drawing temperature causing grain coarsening, and avoiding excessively low wire drawing temperature causing the temperature of the coil entering the salt bath to be too low, premature precipitation of network carbides, or insufficient quenching martensite phase change.
[0049] Furthermore, after the wire is coiled, it is conveyed to the salt tank via a roller conveyor with a speed of 0.7~1.1m / s. This roller conveyor speed can control the conveying time of the coil from the coiler to the salt tank, adapting to the coiler to smoothly convey the coil to the salt tank, avoiding the roller conveyor speed being too fast and affecting the coiling or stable conveying, and avoiding the roller conveyor speed being too slow and the coil temperature dropping too much and falling below the target temperature of the coil entering the salt tank.
[0050] Furthermore, the roller speed of the pre-treatment molten salt process is 0.4~0.7m / s; this roller speed can be connected to the roller speed before entering the salt tank, controlling the processing time of the wire rod through the pre-treatment molten salt process, avoiding excessively fast roller speed and short processing time leading to reduced martensitic phase transformation and decreased strength, and avoiding excessively slow roller speed and long processing time leading to excessive martensitic phase transformation, increased energy consumption and toughening difficulty.
[0051] Furthermore, the molten salt circulation rate of the pre-treatment molten salt is 640~840t / h, and the molten salt temperature rise is ≤10℃. Using a larger molten salt circulation rate can control the molten salt temperature rise, improve sufficient cooling capacity, suppress pearlite transformation, and promote martensite transformation.
[0052] Furthermore, the roller speed of the subsequent molten salt treatment is 0.5~0.8m / s. This roller speed can control the processing time of the wire rod through the subsequent molten salt treatment, avoiding insufficient plasticity due to excessively fast roller speed and short processing time, and avoiding increased energy consumption and loss of strong plasticity due to excessively slow roller speed and long processing time.
[0053] Furthermore, the molten salt circulation rate in the subsequent molten salt treatment is 450~650t / h, and the molten salt temperature rise is ≤3℃. Appropriately reducing the molten salt circulation rate can control the molten salt temperature rise, control the uniformity of the subsequent molten salt treatment, and reduce production energy consumption.
[0054] Furthermore, during the slow cooling process on the roller conveyor, the wire rod enters the conveyor roller conveyor after exiting the salt tank. The heat insulation cover on the conveyor roller conveyor is closed or its opening is controlled, and hot air at ≥265℃ from the salt tank is blown onto the conveyor roller conveyor. The heat energy from the online molten salt rapid quenching isothermal toughening treatment can be recovered and utilized through the hot air, reducing production energy consumption and promoting the rapid exit of the wire rod from the production line.
[0055] To further illustrate the present invention, a preferred embodiment of the high-strength stranded wire hot-rolled wire rod containing tempered martensite is further described using Example 1 as an example. The hot-rolled wire rod manufacturing method of Example 1 follows the process flow of heating → rolling → wire drawing → online molten salt rapid quenching isothermal toughening treatment → roller table slow cooling → coiling. Specifically:
[0056] The heating process is used to heat a steel billet with a length × width of 220mm × 220mm in a heating furnace to a high temperature steel billet that can be rolled into plasticity. The heating furnace is heated in sequence according to the preheating section, the first heating section, the second heating section and the soaking section. The soaking temperature of the heating furnace is controlled at 1182℃ and the time in the furnace is 280min.
[0057] The rolling process uses a rolling line to roll high-temperature steel billets into wire rods with a diameter of 13.5 mm. During rolling, the initial rolling temperature is controlled at 1079°C, the final rolling temperature is 924°C, and the final rolling reduction is 23%.
[0058] The spinning process is used to turn the wire from the rolling line into coils through the spinning mechanism. The spinning temperature is 920℃. The coils are spread on the roller conveyor and conveyed to the salt tank along the closely spaced roller conveyor. The roller conveyor speed is 1.1m / s.
[0059] The online molten salt rapid quenching isothermal toughening process employs a two-section salt tank with internal molten salt. After coiling, the wire rod is conveyed by rollers through the first section of the salt tank for the initial molten salt treatment. The wire rod is conveyed at a roller speed of 0.7 m / s during the initial molten salt treatment, allowing it to cool down at a rate of 32℃ / s. The initial temperature of the wire rod entering the salt tank during the initial molten salt treatment is 900℃, the molten salt temperature is 320℃, the treatment time is 10s, the molten salt circulation rate is 840t / h, and the molten salt temperature rise is ≤10℃. The wire rod is then conveyed by rollers through the second section of the salt tank for the final molten salt treatment. The wire rod is conveyed at a roller speed of 0.5 m / s during the final molten salt treatment, the molten salt temperature is 560℃, the treatment time is 360s, the molten salt circulation rate is 450t / h, and the molten salt temperature rise is ≤3℃.
[0060] The slow cooling process on the roller conveyor involves controlling the opening of the insulation cover to blow hot air (≥260℃) from above the two salt baths used in the online molten salt rapid quenching isothermal toughening treatment onto the conveyor roller conveyor. The conveyor roller conveyor then transports the wire rod through the insulation cover, controlling the wire rod to cool to 280℃ at a slow cooling rate of 0.5℃ / s. The coiling process involves coiling the wire rod into coils using a coiling drum. After packaging and warehousing, the hot-rolled wire rod is obtained as a finished product, the metallographic structure of which is shown in the figure below. Figure 1 As shown.
[0061] The chemical composition of each embodiment is shown in Table 1 below, with the remainder being Fe and unavoidable impurities.
[0062] Table 1. Chemical composition of each embodiment
[0063]
[0064] The process parameters of the manufacturing methods of each embodiment and comparative example are shown in Table 2 below. The main difference between Comparative Example 1, Comparative Example 2 and Example 1 is that the parameters of the online molten salt rapid quenching isothermal toughening treatment process are different; the main difference between Comparative Example 3, Comparative Example 4 and Example 2 is that the parameters of the online molten salt rapid quenching isothermal toughening treatment process are different; the main difference between Comparative Example 5 and Example 3 is that the parameters of the roller conveyor slow cooling process are different.
[0065] Table 2. Process parameters for each embodiment and comparative example
[0066]
[0067] The microstructure and properties of the hot-rolled wire rods obtained in the above embodiments and comparative examples were tested, and the comparison results are shown in Table 3 below:
[0068] Table 3. Microstructure and property test results of different hot-rolled wire rods
[0069]
[0070] As can be seen from the results in the table above, compared to the high-carbon composition, which often suffers from weakened strengthening due to the low cooling rate during the Stellmore air-cooling phase transformation, and faces the problem of uncontrollable abnormal structures such as network carbides and martensite in the base material, requiring offline heat treatment, this invention, through Nb-V-Mo chemical composition design combined with online molten salt rapid quenching isothermal toughening technology, controls the wire rod to rapidly transition from the high-temperature austenitic state to the martensite phase region after the first stage of molten salt treatment, suppressing network carbides and forming a structure dominated by quenched martensite. The second stage of molten salt treatment promotes the decomposition of untransformed residual austenite into sorbite, and the quenched structure is isothermally tempered to adjust the... The wire rod is controlled to achieve a high degree of plasticity matching. It is then slowly cooled on a roller conveyor to avoid insufficient plasticity due to inadequate cooling. At the same time, the slow cooling promotes further toughening of the wire rod structure and improves the tempering and softening effect, forming a hot-rolled wire rod containing tempered martensite. It can achieve a network carbide level of 0, mechanical property difference between the same ring ≤50MPa, tensile strength of 1623~1673MPa, and reduction of area of 31%~36%. It can effectively suppress abnormal network carbide, achieve multiphase structure control, and quickly control the structure and toughness online. It can be used for the production of ultra-high strength stranded wires such as 2500MPa grade, without offline heat treatment and can reduce the risk of wire breakage in stranded wire manufacturing.
[0071] The comparison results between Comparative Examples 1 and 2 and Example 1 show that higher wire rod entry temperature in the salt bath, lower molten salt temperature in the initial molten salt treatment, lower roller speed, and longer treatment time lead to increased high-temperature austenite to quenched martensite transformation, resulting in improved strength after tempering. However, excessively high wire rod entry temperature in the salt bath, excessively low molten salt temperature in the initial molten salt treatment, and excessively long treatment time increase the difficulty of tempering softening and decrease the wire rod's section shrinkage rate. Conversely, excessively low wire rod entry temperature in the salt bath is detrimental to controlling network carbides, and... If the molten salt temperature in the pre-treatment stage is too high and the treatment time is too short, insufficient quenching will affect the martensitic transformation and result in insufficient wire rod strength. Therefore, the preferred molten salt temperature for the wire rod entering the salt bath is 870~950℃, the molten salt temperature is 280~350℃, and the treatment time is 5~15s. This can control the wire rod to quickly enter the martensitic phase region from the high-temperature austenitic state after the pre-treatment stage, suppress network carbides, and control the formation of an appropriate microstructure dominated by quenched martensite.
[0072] Comparison results of Comparative Examples 3 and 4 with Example 2 show that the lower the molten salt temperature and the shorter the treatment time after the post-treatment of the wire rod, the higher the strength of the wire rod can be maintained. Increasing the molten salt circulation can reduce the fluctuation of mechanical properties. However, if the molten salt temperature and treatment time of the post-treatment are too low, it is not conducive to controlling the phase transformation and the transformation of quenched martensite to tempered martensite. The wire rod contains brittle martensite structure, and the brittleness and mechanical property fluctuations increase. Conversely, if the molten salt temperature and treatment time of the post-treatment are too high, it is not conducive to inhibiting the coarsening of cementite and the ripening and growth of precipitates at high temperature, resulting in insufficient wire rod strength. Therefore, the preferred molten salt temperature for the post-treatment is 560~600℃ and the treatment time is 160~360s. This can promote the decomposition of untransformed residual austenite into sorbite and perform isothermal tempering on the quenched structure to promote the dispersion and distribution of microalloyed carbides, so as to quickly control the strength and plasticity matching of the wire rod.
[0073] The comparison results between Comparative Example 5 and Example 3 show that the slow cooling of wire rod through the roller table can further promote the toughening of the structure, but it is not necessary to use a long treatment with an excessively slow cooling rate. This can balance production efficiency and promote the efficient and stable production of hot-rolled wire rod.
[0074] The detailed descriptions listed above are merely specific illustrations of feasible embodiments of the present invention, and are not intended to limit the scope of protection of the present invention. All equivalent embodiments or modifications made without departing from the spirit of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for manufacturing high-strength stranded wire hot-rolled wire rod containing tempered martensite, characterized in that, Its manufacturing methods include: The hot-rolled wire rod is rolled into production line material according to its chemical composition. The chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.95%~0.99%, Si: 0.87%~1.05%, Mn: 0.91%~1.12%, Cr: 0.45%~0.65%, Nb: 0.025%~0.040%, V: 0.025%~0.040%, Mo: 0.35%~0.55%, P≤0.015%, S≤0.015%, with the remainder being Fe and unavoidable impurities. The wire rod is produced by spinning into coils and then undergoes online molten salt rapid quenching isothermal toughening treatment. The coils first undergo a preliminary molten salt treatment with a cooling rate of ≥30℃ / s. The temperature of the coil entering the salt bath in the preliminary molten salt treatment is 870~940℃, the molten salt temperature is 280~350℃, and the treatment time is 5~15s. Then, it undergoes a subsequent molten salt treatment with a molten salt temperature of 560~600℃ and a treatment time of 160~360s. Finally, it undergoes slow cooling on a roller conveyor, where the coils are slowly cooled to 280℃ or below at a cooling rate of 0.25~0.55℃ / s, resulting in a hot-rolled coil with a microstructure consisting of tempered sorbite, tempered martensite, and ferrite. The hot-rolled wire rod has a diameter of 5.5~16mm, a volume fraction of tempered sorbite of 32%~44%, a lamellar spacing of 50~70nm, a volume fraction of tempered martensite of 55%~65%, a network carbide grade of 0, a mechanical property difference of ≤50MPa between rings, a tensile strength of 1623~1673MPa, and a reduction of area of 31%~36%.
2. The method for manufacturing high-strength stranded wire containing tempered martensite hot-rolled wire rod according to claim 1, characterized in that, Before rolling, a rectangular steel billet with a side length of 180mm to 220mm is heated. During heating, the uniform heating temperature of the heating furnace is controlled at 1150 to 1220℃, and the furnace time is 150 to 280 minutes.
3. The method for manufacturing high-strength stranded wire containing tempered martensite hot-rolled wire rod according to claim 1, characterized in that, The initial rolling temperature is controlled at 1040~1090℃, the final rolling temperature at 900~940℃, and the final rolling reduction at 23%~28%.
4. The method for manufacturing high-strength stranded wire containing tempered martensite hot-rolled wire rod according to claim 1, characterized in that, The spinning temperature is 890~930℃.
5. The method for manufacturing high-strength stranded wire containing tempered martensite hot-rolled wire rod according to claim 1, characterized in that, The wire is spun into coils and then conveyed to the salt tank via roller conveyors at a speed of 0.7~1.1m / s.
6. The method for manufacturing high-strength stranded wire containing tempered martensite hot-rolled wire rod according to claim 1, characterized in that, The roller speed of the front section molten salt treatment is 0.4~0.7m / s; the roller speed of the rear section molten salt treatment is 0.5~0.8m / s.
7. The method for manufacturing high-strength stranded wire containing tempered martensite hot-rolled wire rod according to claim 1, characterized in that, The molten salt circulation rate of the front-end molten salt treatment is 640~840t / h, and the molten salt temperature rise is ≤10℃.
8. The method for manufacturing high-strength stranded wire containing tempered martensite hot-rolled wire rod according to claim 1, characterized in that, The molten salt circulation rate of the subsequent molten salt treatment is 450~650t / h, and the molten salt temperature rise is ≤3℃.
9. A hot-rolled wire rod containing tempered martensite for high-strength stranded wire, characterized in that, The hot-rolled wire rod is manufactured by the manufacturing method of high-strength stranded wire rod containing tempered martensite as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Wire rod for 2500MPa grade steel strand and its manufacturing method
CN112176258B
Wire rod for 2500-2560MPa-grade stress corrosion resistant prestressed steel strand, steel strand and production method
CN120400683A
Hot-rolled wire rod for 2360MPa-grade stranded wire and manufacturing method of hot-rolled wire rod
CN121518918A
High-strength complex-phase hot-rolled wire rod for 2360MPa-grade stranded wire and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN121518919A